56.2k views
2 votes
Write the expression. With a single base and single positive exponent then simplify. The base price is ?The exponent is ?This simplifies to ?

Write the expression. With a single base and single positive exponent then simplify-example-1
User Tendinitis
by
5.5k points

1 Answer

6 votes

given :


y^(-4)(y^2)^2

let us simplify.


\begin{gathered} =y^(-4)(y^2)^2 \\ =y^(-4)y^4 \\ =y^(-4+4) \\ =y^0 \\ =1 \end{gathered}

The base is y

The exponent is 0

This simplifies to 1.

User Pazof
by
5.2k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.